The EU's tightrope walk to energy cooperation with Central Asia: Are they heading towards an enhanced cooperation? - Kizekova, Alica (Friedrich-Ebert-Stiftung, 2024)
This paper addresses the EU’s engagements with Kazakhstan, Kyrgyzstan, Tajikistan, Uzbekistan, and Turkmenistan in Central Asia in the energy sector in the era of geopolitical instability and the heightened focus on energy security, diversification of energy supply, and energy transition. The states in Central Asia could play an important role in the EU’s quest to fulfill its energy needs. Furthermore, some actors voice positive pro-climate rhetoric, claiming ambitious renewable energy targets that could be seen as a potential bridge for a more substantive cooperation with the EU. However, despite the potential and already signed joint agreements, the EU has not taken full advantage of the regional resource potential. Why does this still feel like an uncompleted mission? Are there promising prospects for overcoming the current obstacles and achieving the energy transition goals?